Letter (copy) : International Brigade - McDonald, Florence
034-0140-001 Secretary's. FEM/FP/3 12th September, 1938. PRIVATE. Mr. G.T. Owen, 66, Wern Road, Margam, Port Talbot. Dear Sir, INTERNATIONAL BRIGADE. I am writing to acknowledge your confidential letter addressed to Sir Walter Citrine, asking for his assistance in expediting the repatriation of the British men who have been fighting with the International Brigade in Spain. As soon as Sir Walter returns to London your letter will be placed before him. Yours faithfully, Private Secretary. 292/946/34/140